2014
DOI: 10.2196/resprot.3270
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Lifting at Work and Risk of Ischemic Heart Disease: Protocol for a Register-Based Prospective Cohort Study

Abstract: BackgroundThere are theoretical grounds to suspect that heavy lifting at work is an important risk factor for ischemic heart disease (IHD). However the relationship has not been sufficiently acknowledged by empirical studies. Positive and statistically significant associations have been found in studies that utilize self-reported exposure data. Such studies are, however, prone to reporting bias. All else equal, people with a poor cardiovascular fitness/health may have a higher propensity to perceive their work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Therefore, we cannot rule out the possibility that a significant effect from heavy lifting has been missed (offset) by the factors which we could not control for. We know, however, from collateral data [16] that the nullfinding is unlikely to be explained by differences in BMI and smoking habits. We can also rule out confounding from socio-economic status, since in the study we only included blue-collar workers.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Therefore, we cannot rule out the possibility that a significant effect from heavy lifting has been missed (offset) by the factors which we could not control for. We know, however, from collateral data [16] that the nullfinding is unlikely to be explained by differences in BMI and smoking habits. We can also rule out confounding from socio-economic status, since in the study we only included blue-collar workers.…”
Section: Discussionmentioning
confidence: 90%
“…By including the total target population in the analyses, we eliminated volunteer bias, and by using job codes as a proxy for occupational exposure, we eliminated reporting bias. We also eliminated hindsight bias through the publication of our study protocol [16], in which all hypotheses and statistical models were specified carefully before we looked at any relation between the exposure and response variables in our data material. The large number of participants gave us an extraordinary high statistical power, and the prospective design ascertained that the exposure took place before the outcome.…”
Section: Primary Statistical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Also the collection of BP only in consultation during rest is a limitation due to the lower prognostic value than obtained by monitoring of 24 hours BP or BP during sleep 33,34 . Furthermore, a previous study has shown occupational lifting to reduce the odds for having prolonged working hours 35 , however this is not possible to adjust for in the present analysis due to the lacking information of amount of weekly working hours.…”
Section: Methodological Challengesmentioning
confidence: 92%